The path made clear : discovering you life's direction and purpose - Winfrey, Oprah (New York : Flatiron Books, 2019)
"In [this book], Oprah shares what she sees as a guide for activating your deepest vision of yourself, offering the framework for creating not just a life of success, but one of significance. The book's ten chapters are organized to help you recognize the important milestones along the road to self-discovery, laying out what you really need in order to achieve personal contentment, and what life's detours are there to teach us. Oprah opens each chapter by sharing her own key lessons and the personal stories that helped set the course for her best life. She then brings together wisdom and insights from luminaries in a wide array of fields, inspiring readers to consider what they're meant to do in the world and how to pursue it with passion and focus. Renowned figures such as Eckhart Tolle, Brene Brown, Lin-Manuel Miranda, Elizabeth Gilbert, Jay-Z, and Ellen DeGeneres share the greatest lessons from their own journeys toward a life filled with purpose"--
The seeds -- The roots -- The whispers -- The clouds -- The map -- The road -- The climb -- The give -- The reward -- Home.
"An Oprah book."
"Produced by Melcher Media."
Keywords: Life; Self-actualization (Psychology); Meaning (Philosophy); Positive psychology; Self-help publications